Dynamics of logarithmic negativity and mutual information in smooth quenches. (6th July 2020) - Fujita, Hiroyuki; Nishida, Mitsuhiro; Nozaki, Masahiro; Sugimoto, Yuji
Abstract: We study the time evolution of mutual information (MI) and logarithmic negativity (LN) in two-dimensional free scalar theory with two kinds of time-dependent masses: one time evolves continuously from non-zero mass to zero; the other time evolves continuously from finite mass to finite mass, but becomes massless once during the time evolution. We call the former protocol ECP, and the latter protocol CCP. Through numerical computation, we find that the time evolution of MI and LN in ECP follows a quasi-particle picture except for their late-time evolution, whereas that in CCP oscillates. Moreover, we find a qualitative difference between MI and LN which has not been known so far: MI in ECP depends on the slowly moving modes, but LN does not.